Peculiarities of the composition of surface and groundwater in eastern Ukraine during the war: assessment of environmental and carcinogenic risks - O. O. Kovalov; Yu. M. Kolesnyk; A. I. Sevalniev; L. P. Sharavara; O. V. Hancheva; K. O. Kovalov; T. M. Tyshchenko; Ye. O. Tulushev (Сучасні медичні технології)
Russia’s war against Ukraine has devastating humanitarian, social, economic and environmental consequences. To assess them, it is important to monitor environmental pollutants in the eastern regions of Ukraine. This study analyses the chemical composition of surface and groundwater near the frontline in Zaporizhzhia region and justifies the need to develop a state plan for the restoration of damaged areas.